Modeling and optimization strategies for improving human resource management effectiveness in private elementary schools: the role of personality, organizational climate, achievement motivation, and knowledge management - Mei Tri Listari; Soewarto Hardhienata; Dian Wulandari (Education and Social Sciences Review, 2026)
This study aims to (1) examine the direct effects of personality, organizational climate, and achievement motivation on HRM effectiveness; (2) investigate the mediating role of achievement motivation and knowledge management; and (3) develop optimization strategies using the SITOREM approach. A mixed-methods design combining exploratory qualitative and quantitative causal approaches (POP-SDM method) was employed. Data were collected from 144 principals and teachers in private elementary schools with "A" (superior) accreditation in Bogor Regency, Indonesia, selected through area-cluster proportional random sampling. Path analysis and SITOREM analysis were used for hypothesis testing and indicator optimization. Personality (β=0.307, p<0.001), organizational climate (β=0.232, p<0.001), and achievement motivation (β=0.206, p<0.005) had significant positive direct effects on HRM effectiveness. Personality (β=0.251, p<0.001) and organizational climate (β=0.307, p<0.001) significantly influenced achievement motivation. Indirect effects through achievement motivation were significant for both personality (β=0.077, p<0.001) and organizational climate (β=0.142, p<0.001). Knowledge management mediated the personality→HRM effectiveness (total effect=0.492) and organizational climate→achievement motivation (total effect=0.333) relationships. SITOREM analysis identified five priority indicators requiring improvement: extraversion, work mechanisms, responsibility, knowledge application, and knowledge retention. HRM effectiveness in accredited private elementary schools is enhanced through integrated strengthening of personality, organizational climate, achievement motivation, and knowledge management. School leaders should prioritize interventions targeting the five low-performing indicators identified through SITOREM analysis.